Eksistensi Tradisi Metawa dalam Prespektif Civic Culture pada Masyarakat Mandar di Desa Tanjung Lalak - Taskiatun Nisa; Mariatul Kiptiah (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Civic culture plays an essential role in shaping a harmonious society through values such as mutual respect, politeness, and social responsibility. However, the current wave of globalization and digital technology penetration trigger shifts in social behavior patterns and erode the sustainability of local wisdom. This study aims to analyze the existence of the metawe tradition a local wisdom of greeting and maintaining etiquette from the Mandar ethnic group within the perspective of civic culture in Tanjung Lalak Village, Kotabaru Regency. The method employed is descriptive qualitative, with data source determination techniques through purposive sampling and snowball sampling. Data collection was conducted via observation, in-depth interviews, and documentation. The results indicate that the metawe tradition remains alive as an instrument for preserving general politeness through the habits of greeting, bowing the body, and maintaining spoken words. Condition comparison reveals situational tension; prior to the study, the younger generation was considered indifferent due to gadgets, but research revealed they still internalize this value as an "automatic brake" in social interaction, yet hesitate to respond to the changing public sphere. This study suggests formally integrating traditional values into strengthening civic disposition